SIMULASI CURAH HUJAN BULANAN KOTA PALEMBANG DENGAN JARINGAN SYARAF TIRUAN - Fadhila Firdausa (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2020)
Rainfall is one of the important data used in the involvement of infrastructure development, irrigation, agriculture and others.The development of science and technology has reached the stage of progress towards the era of digitalization.Consequently new software is needed to support the progress of science and technology.One of the software that has been developed at this time is matlab software. The method used in the simulation is Artificial Neural Networks (ANN) which are analyzed using Matlab. Artificial Neural Network is a method that has the ability to imitate the input data entered into a simulation.Artificial Neural Networks has been widely used in research.Therefore in this research, it will use Artificial Neural Networks to process rainfall data Palembang city.Rainfall data used is monthly rainfall data from 2016 until 2018.In the results of research that has been carried out obtained the smallest error of 1.84% and stopped at 25000 epoch trial.The distribution of monthly rainfall data in the dry season affects the ANN simulation, causing an error to be large in the dry month.